Bauran Promosi Mempengaruhi Pengambilan Keputusan Mahasiswa Memilih Universitas Muhammadiyah Bengkulu - Mukhlizar Mukhlizar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine advertising (X1), sales promotion (X2) personal selling (X3) publicity (X4) direct marketing (X5) partially and simultaneously have a significant effect on student decision making choosing Muhammadiyah University Bengkulu. This study uses a quantitative approach with explanatory research methods, primary data sources through questionnaires, secondary data from information publications and other sources. Questionnaires were distributed to 193 research samples from 2018-2019 students. The results showed that of the five promotion mix variables, there were three variables that partially had a significant effect on student decision making, namely advertising, public relations, and direct marketing variables, while those that had no significant effect were sales promotion and personal selling variables. Simultaneously the promotion mix includes advertising (X1), sales promotion (X2), personal selling (X3), public relations (X4) and direct marketing (X5) have a significant effect on student decision making. Keywords: Promotional Mix, Choice Decision